The impact of an innovative community-based peer-led intervention on uptake and coverage of sexual and reproductive health services among adolescents and young people 15-24 years old: results from the Yathu Yathu cluster randomised trial - Mwelwa Muleba Phiri; Albertus Schaap; Bernadette Hensen; Lucheka Sigande; Melvin Simuyaba; Lawrence Mwenge; Rosemary Zulu-Phiri; Louis Mwape; Sian Floyd; Sarah Fidler; Richard Hayes; Musonda Simwinga; et al. (BMC, 2024)
Abstract Background The Yathu Yathu ("For Us, By Us") cluster-randomized trial (CRT) evaluated a peer-led community-based sexual and reproductive health(SRH) intervention implemented to address persistent barriers to SRH service use among adolescents and young people (AYP). We report the impact of the intervention on coverage of key SRH services among AYP. Methods The trial was conducted from Jul 2019-Oct 2021 in two urban communities in Lusaka, Zambia, divided into 20 zones (~ 2350 AYP/zone). Zones were randomly allocated to intervention (N = 10) or control (N = 10) arm. In all zones, a census was conducted and all AYP aged 15-24-years offered participation. The intervention consisted of peer-led community-based hubs providing SRH services; a prevention points card (PPC) system to incentivize and track SRH service use and community engagement. This paper reports on the outcome of coverage (accessing at least one key SRH service), comparing intervention and control arms using PPC data and standard methods of analysis for CRTs. Results Among enumerated AYP, 93.6% (14,872/15,894) consented to participate from intervention zones and 95.1% (14,500/15,255) from control zones. Among those who accepted a PPC, 63.8% (9,493/14,872) accessed at least one key SRH service during the study period in the intervention arm, compared to 5.4% (776/14,500) in the control arm (adjPR 12.3 95%CI 9.3-16.2, p < 0.001). Conclusions The Yathu Yathu intervention increased coverage of key SRH services among AYP and reached two-thirds of AYP. These findings demonstrate the potential of providing peer-led community-based SRH services. Trial registration ISRCTN75609016 (11/10/2021), clinicaltrials.gov number NCT04060420 (19/08/2019); retrospectively registered.